(untitled) (Bangladesh Journal of Medical Science, 2020)
Background: Dengue has become an important public health problem in the world. It is an infectious disease caused by dengue virus and transmitted by Aedes mosquito. The understanding the knowledge, attitude and practice (KAP) of the general community on dengue prevention are helpful to give information for good strategic planning and engaged the community with dengue control. The knowledge on preventive measures in dengue is important to decrease the mortality rate, but the implementation of knowledge among individuals to reduce dengue is still an issue. Study Objectives: This study aims to examine the KAP regarding dengue among International Islamic University of Malaysia (IIUM) Kuantan students. Besides that, this study also aims to find the factors associated with KAP of dengue and to assess the relationship between KAPs regarding dengue among IIUM Kuantan students. Methods: This study used cross-sectional study, and 135 respondents were selected by using convenience sampling method. The questionnaire consists of 67 questions which were divided into four parts (socio-demographic characteristic, knowledge regarding dengue, the attitude of dengue and practice on prevention of dengue). In this study, to evaluate the KAP of dengue among students in IIUM Kuantan. Independent t-test, Kruskal-Wallis test, Mann-Whitney test, and Pearson test were used to find all related factors influencing KAP of dengue. Results: This study shows that the level of KAP of dengue among students in IIUM Kuantan was relatively high. All the respondents have very good level of KAP towards dengue prevention, symptoms and transmission. There was a significant difference in attitude among marital statuses (p=0.004). The students from FOM had better knowledge (p=<0.001) as compared to FOD and better attitude scores than KOP (p=0.001). This study also depicted that dengue knowledge-attitude towards dengue prevention was significantly correlated (p=0.005). Conclusion: the KAP regarding dengue among IIUM Kuantan students was good. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.245-253